IMPACT OF ADDING NKL AND FERMIPAN YEAST: MICROBIAL POPULATION AND DISCOLORATION OF COCOA BEAN “ASALAN” CHIPS DURING FERMENTATION - Hermiza Mardesci; Ratri Retno Utami; Mulono Apriyanto (BBSPJI Hasil Perkebunan, Mineral Logam, dan Maritim, 2023)
The study aims to determine the effect of adding microbes to the fermentation process of